Proceedings IEEE European Test Workshop
DOI: 10.1109/etw.2000.873783
|View full text |Cite
|
Sign up to set email alerts
|

Test challenges in nanometer technologies

Abstract: Scaling transistor feature size allows greater density, higher performance and lower cost. The unrelenting pursuit of device scaling has enabled MOS gate dimensions to be reduced from IO-m in the 1970's to a present day size of 0.1-m. Conventional scaling of gate oxide thickness, source/drain extension, junction depths, and gate lengths have brought about several new technology issues invalidating some earlier methods for testing ICs. To enable testing devices into the 21'' century, new approaches are required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…[142,24,143] and recent research [151,149,150] has reported negative impact on manufacturing test quality. In particular, as it will be shown in this chapter, process variation influences the behaviour of resistive bridging faults (RBF), which is a major defect type in CMOS [64].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[142,24,143] and recent research [151,149,150] has reported negative impact on manufacturing test quality. In particular, as it will be shown in this chapter, process variation influences the behaviour of resistive bridging faults (RBF), which is a major defect type in CMOS [64].…”
Section: Discussionmentioning
confidence: 97%
“…Process variation causes the manufactured chips to deviate from the specification to which they were designed [142,143], including variations in delay and leakage power [24].…”
Section: Process Variation-aware Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, as the dimensions of manufactured devices decrease, new more complex memory faults are observed that require specialized memory tests to ensure their detection [24]. Keeping in mind that the allowed defect per million (DPM) budget for the entire collection of on-chip memory is extremely low, these trends stress the increasing importance of memory testing in microprocessors today and in the future [33].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of copper wiring will shift the predominant failure mode from shorts and bridges to opens [2]. Needham [3] reports that opens were the most likely cause of field returns of Intel microprocessors.…”
Section: Introductionmentioning
confidence: 98%